(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article investigates the influence of pedagogical skills on the formation of students’ desire to achieve set goals and their involvement in active activity, which determines the effectiveness of the motivational process. The author considers stimulation as a multi-component process that encompasses interrelated aspects: goals, content, forms, methods and means of pedagogical interaction. The psychological, age and gender characteristics of students, their previous experience and learning style are taken into account. Special emphasis is placed on creative cooperation in the interaction "teacher-student". It is proven that external stimuli are an important factor in the activation of educational activity and self-development. Organizational and methodological approaches to the formation and strengthening of professional self-development of physical education teachers are considered. It is determined that self-development is a key element of professional development, its structural components and stimulation mechanisms are analyzed. Effective methodological approaches that contribute to the development of professional competencies of teachers are substantiated, in particular through the use of innovative educational technologies, self-education, reflective activity and mentoring. Special attention is paid to the organizational aspects of improving the training of physical education teachers in conditions of continuous education. The model of activating professional self-development is analyzed, which takes into account modern trends in the field of education and physical education. Effective strategies for the development of professional reflection, independent educational and cognitive activity and the introduction of modern pedagogical technologies into professional activity are highlighted.